Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Emosi Anak Di TK Lazuardi Kamila Global Islamic School Surakarta Tahun Ajaran 2015/2016 - Ambarwati, Nita; , Drs. Ilham Sunaryo, M.Pd, AUD (2016)
Permissive parenting is parenting that delivered all the behaviour to children, parents tend to spoil the child and little in giving punishment to the child, handed over all decisions to the children, lack of control in their parents and their demands. Usually children with permissive parenting,they tend to be selfish, do not comply with existing regulations or their own way and lack of responsibility. They are also difficult in controlling emotions such as children tend to be spoiled, don't want to budge, and little regard for the feelings of others because the child get used to all the wishes should be followed. The purpose of this research is to know the permissive parenting relationships on the development of children's emotion in Lazuardi Kamila Global Islamic School Kindergarten of Surakarta Academic Year 2014/2015. This type of research descriptive corelational research. The research was carried out in Lazuardi Kamila Global Islamic School Kindergarten of Surakarta. Sample research was 73 children they are class A and B, the technique of sampling is simple random sampling. Data analysis techniques using the product moment correlations. Based on the results of the analysis of the data obtained the result was that there was a relationship between parenting parents are permissive toward the development of emotions children in Lazuardi Kamila Global Islamic School Kindergarten in Surakarta Academic Year 2015/2016. This was proved by the results of r pearson- correlation 0.325 with significance of 0.005 < 0.01 (p = 0.005; p < 0.01) which means that it had denied ho's relationship between parenting parents were permissive with children's emotional development Lazuardi Kamila Global Islamic School Kindergarten of Surakarta Academic Year 2015/2016. Keywords : The child's emotional development, parenting parents